Silicon-carbon composite negative electrode material and preparation method thereof
Patent Information
- Application Number
- CN202311515459.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-15
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-11-15
AI Technical Summary
[0005]有鉴于此,本发明提供了一种硅碳复合负极材料及其制备方法,以解决现有方案制备的硅碳复合负极材料膨胀率大,循环性能差,有些采用多孔基体的方案存在稳定性差以及金属元素含量偏高、不易分离的问题
[0024]1、本发明公开的硅碳复合负极材料在制备过中通过真空热处理,实现硅颗粒的蒸发,获得自设计的多孔碳骨架(多孔碳骨架前驱体),该骨架是三维多孔结构,强度远高于普通多孔碳骨架,并且结构更加稳定;此外还具有不含有金属元素的特点;
Smart Images

Figure BDA0004548887290000131
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery anode material technology, and in particular to a silicon-carbon composite anode material and its preparation method. Background Technology
[0002] Lithium-ion rechargeable batteries are characterized by high quality, high volumetric energy density, long cycle life, and low self-discharge performance, making them widely used in portable electronic products, electric vehicles, and energy storage. However, the traditional combination of graphite and cathode materials cannot meet market demands. Therefore, there is an urgent need to find a cathode material with high specific capacity. Although Si, as a cathode material, has a theoretical capacity as high as 4200 mAh / g, its expansion of up to 300% significantly affects cycle performance, thus limiting its market promotion and application.
[0003] Currently, nano-sizing is the main method to alleviate Si anode expansion, such as making silicon into nanospheres and nanowires. However, conventional grinding methods can only control the Si particle size to around 100nm. Furthermore, excessive nano-sizing can increase the specific surface area of the material, affecting its processing and performance. To address the bottleneck of controlling Si particle size using traditional grinding methods, patent CN 115966684A uses porous carbon as a matrix and obtains a silicon-carbon composite material with Si nanoscales <10nm through silane deposition. However, the porous carbon matrix used in this method suffers from unstable pore structure collapse during cycling. Patent CN114956046A uses a self-made metal MOF material as a matrix and deposits Si in the metal MOF material through silane deposition to obtain a silicon-carbon composite anode material. However, the MOF matrix prepared by these methods has a high metal element content, making it difficult to separate.
[0004] Therefore, how to disclose a silicon-carbon composite anode material and its preparation method, improve the stability of porous carbon matrix, and reduce the metal element content in the matrix is an urgent problem to be solved in this field. Summary of the Invention
[0005] In view of this, the present invention provides a silicon-carbon composite anode material and its preparation method to solve the problems of large expansion rate, poor cycle performance, poor stability, high metal element content, and difficulty in separation of silicon-carbon composite anode materials prepared by existing schemes.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A method for preparing a silicon-carbon composite anode material includes the following steps:
[0008] 1) Si powder is mixed and ground with an organic solvent to obtain a mixed slurry. Then the mixed slurry is mixed with carbon nanotubes and dried to obtain a mixed powder precursor.
[0009] 2) The mixed powder precursor obtained in step 1) is mixed with an organic carbon source and then sintered and vacuum heat treated in sequence to obtain a porous carbon framework precursor.
[0010] 3) Deposit silicon particles on the porous carbon framework precursor obtained in step 2) to obtain silicon-carbon composite anode material.
[0011] Preferably, the particle size of the Si powder in step 1) is 3–10 μm;
[0012] The organic solvent includes one or more of methanol, ethanol, ethylene glycol, propanol, isopropanol, and propylene glycol.
[0013] Preferably, the solid content of the mixed slurry in step 1) is 10-50%; the mass ratio of the carbon nanotubes to the mixed slurry is 0.1-5:100.
[0014] Preferably, the organic carbon source in step 2) includes one or more of asphalt, phenolic resin, sucrose, glucose, and citric acid;
[0015] The mass ratio of the organic carbon source to the total mass of the organic carbon source and the mixed powder precursor is 45–90:100.
[0016] Preferably, the sintering temperature in step 2) is 300–1000°C, and the sintering time is 3–24 h.
[0017] Preferably, in step 2), the vacuum degree of the vacuum heat treatment is 0-1000 Pa, the temperature of the vacuum heat treatment is 700-1500 °C, and the time of the vacuum heat treatment is 3-24 h.
[0018] Preferably, the step of depositing silicon particles in step 3) is as follows: first, silicon particles are deposited on the porous carbon framework precursor by a mixture of silane gas and protective gas, and then a carbon layer is deposited by a mixture of carbon source gas and protective gas.
[0019] Preferably, the volume ratio of silane gas to protective gas in the mixture of silane gas and protective gas is 1:1 to 10; the silane gas includes methanesilane and / or ethylsilane, and the protective gas includes one or more of nitrogen, helium, neon and argon.
[0020] The volume ratio of carbon source gas to protective gas in the mixture of carbon source gas and protective gas is 1:1 to 10; the carbon source gas includes one or more of methane, ethane, propane, acetylene and propyne, and the protective gas includes one or more of nitrogen, helium, neon and argon.
[0021] Preferably, the mass ratio of Si to silicon-carbon composite anode material in the silicon-carbon composite anode material is 1 to 9:10.
[0022] Another object of the present invention is to provide a silicon-carbon composite anode material prepared by the preparation method described above.
[0023] As can be seen from the above technical solution, compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The silicon-carbon composite anode material disclosed in this invention is prepared by vacuum heat treatment to evaporate silicon particles and obtain a self-designed porous carbon framework (porous carbon framework precursor). This framework is a three-dimensional porous structure with much higher strength than ordinary porous carbon frameworks and a more stable structure. In addition, it also has the characteristic of not containing metal elements.
[0025] 2. The present invention also discloses the preparation of a mixed powder precursor by mixing carbon nanotubes with a mixed slurry, which can improve the electrical conductivity of the obtained porous carbon framework precursor composite material.
[0026] 3. The silicon-carbon composite anode material obtained by the silane vapor deposition method in this invention has a Si particle size of less than 10 nm. For silicon-based anodes, the smaller the size, the faster the lithium-ion transport and the better the relative performance. The silicon-carbon composite anode material prepared by this invention has excellent electrochemical performance, with a capacity of 1800-2200 mAh / g, an initial efficiency of 88-92%, and a capacity retention rate of 92.5% after 50 cycles. Detailed Implementation
[0027] This invention provides a method for preparing a silicon-carbon composite anode material, comprising the following steps:
[0028] 1) Si powder is mixed and ground with an organic solvent to obtain a mixed slurry. Then the mixed slurry is mixed with carbon nanotubes and dried to obtain a mixed powder precursor.
[0029] 2) The mixed powder precursor obtained in step 1) is mixed with an organic carbon source and then sintered and vacuum heat treated in sequence to obtain a porous carbon framework precursor.
[0030] 3) Deposit silicon particles on the porous carbon framework precursor obtained in step 2) to obtain silicon-carbon composite anode material.
[0031] In this invention, the particle size of the Si powder in step 1) is 3 to 10 μm, specifically 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, or 9 μm.
[0032] In this invention, the organic solvent includes one or more of methanol, ethanol, ethylene glycol, propanol, isopropanol, and propylene glycol.
[0033] In this invention, the solid content of the mixed slurry in step 1) is 10-50%. Specifically, it can be 15%, 20%, 25%, 30%, 35%, 40%, or 45%. The mass ratio of the carbon nanotubes to the mixed slurry is 0.1-5:100, preferably 0.5-4:100, more preferably 1-3:100, and even more preferably 2:100.
[0034] In this invention, the organic carbon source in step 2) includes one or more of asphalt, phenolic resin, sucrose, glucose, and citric acid.
[0035] In this invention, the mass ratio of the organic carbon source to the total mass of the organic carbon source and the mixed powder precursor is 45-90:100, preferably 50-80:100, more preferably 60-70:100, and even more preferably 65:100.
[0036] In this invention, the sintering temperature in step 2) is 300-1000℃, specifically 400℃, 500℃, 600℃, 700℃, 800℃, or 900℃; the sintering time is 3-24h, specifically 5h, 8h, 10h, 12h, 15h, 18h, 20h, or 22h.
[0037] In this invention, the vacuum degree of the vacuum heat treatment in step 2) is 0 to 1000 Pa, specifically 50 Pa, 100 Pa, 200 Pa, 400 Pa, 500 Pa, 600 Pa, or 800 Pa; the vacuum heat treatment temperature is 700 to 1500 °C, specifically 800 °C, 900 °C, 1000 °C, 1100 °C, 1200 °C, 1300 °C, or 1400 °C; and the vacuum heat treatment time is 3 to 24 h, specifically 4 h, 5 h, 8 h, 10 h, 12 h, 15 h, 18 h, 20 h, or 22 h.
[0038] In this invention, the step of depositing silicon particles in step 3) is as follows: first, silane is deposited on the porous carbon framework precursor by a mixture of silane gas and protective gas, and then a carbon layer is deposited by a mixture of carbon source gas and protective gas.
[0039] In this invention, the volume ratio of silane gas to protective gas in the mixture of silane gas and protective gas is 1:1 to 10, preferably 1:2 to 8, more preferably 1:4 to 6, and even more preferably 1:5; the silane gas includes methanesilane and / or ethylsilane, and the protective gas includes one or more of nitrogen, helium, neon and argon.
[0040] In this invention, the deposition temperature of the silicon particles is preferably 400-600℃, specifically 420℃, 450℃, 460℃, 480℃, 500℃, 520℃, 550℃, 560℃, and 580℃.
[0041] In this invention, the volume ratio of carbon source gas to protective gas in the mixed gas is 1:1 to 10, preferably 1:2 to 8, more preferably 1:4 to 6, and even more preferably 1:5; the carbon source gas includes one or more of methane, ethane, propane, acetylene, and propyne, and the protective gas includes one or more of nitrogen, helium, neon, and argon. The purpose of depositing the carbon source is to form a carbon layer on the surface of silicon particles to protect the active silicon from oxidation and failure, while simultaneously improving the electrical conductivity of the material.
[0042] In this invention, the deposition temperature of the carbon source is preferably 500 to 1000°C, specifically 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, or 950°C.
[0043] In this invention, the mass ratio of Si to silicon-carbon composite anode material in the silicon-carbon composite anode material is 1 to 9:10, preferably 2 to 8:10, further preferably 4 to 6:10, and even more preferably 5:10; the silicon-carbon composite anode material disclosed in this invention contains only silicon and carbon elements.
[0044] The present invention also provides a silicon-carbon composite anode material prepared by the aforementioned preparation method.
[0045] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0046] Example 1
[0047] S1. Add Si powder with a particle size of 8-10 μm to methanol with a solid content of 10%, and grind for 1 hour to obtain mixed slurry Q1.
[0048] S2. Add 0.1 parts of single-walled carbon nanotubes to 100 parts of the mixed slurry Q1 obtained in S1, stir for 1 hour, and then dry to obtain the mixed powder precursor Q2.
[0049] S3. Mix the powder precursor Q2 obtained in S2 with asphalt, with an asphalt addition ratio of 45%. After mixing, press and sinter the mixture at a sintering temperature of 300℃ and a holding time of 3h. After cooling in the furnace, crush the mixture to obtain the powder precursor Q3.
[0050] S4. Add the Q3 precursor obtained in S3 into a vacuum deposition furnace, vacuum evaporation temperature 700℃, vacuum degree 100Pa, evaporation time 3h, and obtain porous carbon framework precursor Q4 after furnace cooling.
[0051] S5. The Q4 precursor obtained in S4 is added to a rotary kiln. Silane is introduced under nitrogen protection, with a silane-to-nitrogen gas flow rate ratio of 1:10 and a deposition temperature of 500℃. After silicon particle deposition, methane is introduced under nitrogen protection, with a methane-to-nitrogen gas flow rate ratio of 1:10 and a deposition temperature of 800℃. The carbon deposition amount is 5% of the total mass of the anode material. In the silicon-carbon composite anode material, Si:C = 1:9. After deposition, the furnace is cooled to obtain a novel silane-deposited silicon-carbon anode material.
[0052] Example 2
[0053] S1. Add Si powder with a particle size of 6-9 μm to propylene glycol with a solid content of 50%, and grind for 24 hours to obtain mixed slurry Q1.
[0054] S2. Add 5 parts of single-walled carbon nanotubes to 100 parts of the mixed slurry Q1 obtained in S1, stir for 6 hours, and spray dry to obtain the mixed powder precursor Q2.
[0055] S3. Mix the powder precursor Q2 obtained in S2 with phenolic resin, with the phenolic resin addition ratio being 90%. After mixing, press and sinter the mixture at a sintering temperature of 1000℃ and a holding time of 24h. After cooling in the furnace, crush the mixture to obtain the powder precursor Q3.
[0056] S4. Add the Q3 precursor obtained in S3 into a vacuum deposition furnace. Vacuum evaporation temperature is 1500℃, vacuum degree is 500Pa, evaporation time is 24h, and porous carbon framework precursor Q4 is obtained after furnace cooling.
[0057] S5. The Q4 precursor obtained in S4 is added to a rotary kiln. Silane is introduced under nitrogen protection, with a silane-to-nitrogen gas flow rate ratio of 1:1 and a deposition temperature of 600℃. After silicon particle deposition, methane is introduced under nitrogen protection, with a methane-to-nitrogen gas flow rate ratio of 1:1 and a deposition temperature of 1000℃. The carbon deposition amount is 3% of the total mass of the anode material. In the silicon-carbon composite anode material, Si:C = 9:1. After deposition, the furnace is cooled to obtain a novel silane-deposited silicon-carbon anode material.
[0058] Example 3
[0059] S1. Add Si powder with a particle size of 3-6 μm to methanol with a solid content of 20%, and grind for 1 hour to obtain mixed slurry Q1.
[0060] S2. Add 1 part of single-walled carbon nanotubes to 100 parts of the mixed slurry Q1 obtained in S1, stir for 1 hour, and then dry to obtain the mixed powder precursor Q2.
[0061] S3. Mix the powder precursor Q2 obtained in S2 with asphalt, with the asphalt addition ratio being 50%. After mixing, press and sinter the mixture at a sintering temperature of 600℃ and a holding time of 6h. After cooling in the furnace, crush the mixture to obtain the powder precursor Q3.
[0062] S4. Add the Q3 precursor obtained in S3 into a vacuum deposition furnace, vacuum evaporation temperature 800℃, vacuum degree 100Pa, evaporation time 5h, and obtain porous carbon framework precursor Q4 after furnace cooling.
[0063] S5. The Q4 precursor obtained in S4 is added to a rotary furnace. Silane is introduced under nitrogen protection, with a silane-to-nitrogen gas flow rate ratio of 1:10 and a deposition temperature of 500℃. After silicon particle deposition, methane is introduced under nitrogen protection, with a methane-to-nitrogen gas flow rate ratio of 1:10 and a deposition temperature of 800℃. The carbon deposition amount is 10% of the total mass of the anode material. In the silicon-carbon composite anode material, Si:C = 1:1. After deposition, the furnace is cooled to obtain a novel silane-deposited silicon-carbon anode material.
[0064] Example 4
[0065] S1. Add Si powder with a particle size of 5-7 μm to methanol with a solid content of 40%, and grind for 1 hour to obtain mixed slurry Q1.
[0066] S2. Add 3 parts of single-walled carbon nanotubes to 100 parts of the mixed slurry Q1 obtained in S1, stir for 1 hour, and then dry to obtain the mixed powder precursor Q2.
[0067] S3. Mix the powder precursor Q2 obtained in S2 with glucose at a ratio of 60%. After mixing, press and sinter the mixture at a temperature of 800℃ for 10 hours. After cooling in the furnace, crush the mixture to obtain the powder precursor Q3.
[0068] S4. The Q3 precursor obtained in S3 is added to a vacuum deposition furnace. The vacuum evaporation temperature is 1200℃, the vacuum degree is 50Pa, and the evaporation time is 10h. After cooling in the furnace, a porous carbon framework precursor Q4 is obtained.
[0069] S5. The Q4 precursor obtained in S4 is added to a rotary furnace. Silane is introduced under nitrogen protection, with a silane-to-helium flow rate ratio of 1:8 and a deposition temperature of 450℃. After silicon particle deposition, methane is introduced under nitrogen protection, with a methane-to-helium flow rate ratio of 1:10 and a deposition temperature of 700℃. The carbon deposition amount is 5% of the total mass of the anode material. In the silicon-carbon composite anode material, Si:C = 1:5. After deposition, the furnace is cooled to obtain a novel silane-deposited silicon-carbon anode material.
[0070] Comparative Example 1
[0071] Porous carbon material made from pitch (carbonization temperature 900℃, carbonization time 3h) was added to a rotary furnace. Silane was introduced under nitrogen protection, with a silane-to-nitrogen gas flow rate ratio of 1:10 and a deposition temperature of 500℃. After silicon particle deposition, methane was introduced under nitrogen protection, with a methane-to-nitrogen gas flow rate ratio of 1:10 and a deposition temperature of 800℃. The carbon deposition amount was 10% of the total mass of the anode material; the Si:C ratio was 1:1. After deposition, the furnace was cooled to obtain a silicon-carbon anode material.
[0072] Comparative Example 2
[0073] Phenolic resin porous carbon material (carbonization temperature 900℃, carbonization time 3h) was added to a rotary furnace. Silane was introduced under nitrogen protection, with a silane-to-nitrogen gas flow rate ratio of 1:10 and a deposition temperature of 500℃. After silicon particle deposition, methane was introduced under nitrogen protection, with a methane-to-nitrogen gas flow rate ratio of 1:10 and a deposition temperature of 800℃. The carbon deposition amount was 10% of the total mass of the anode material; the Si:C ratio was 1:1. After deposition, the furnace was cooled to obtain the silicon-carbon anode material.
[0074] Experimental Example 1
[0075] The silicon-carbon anode materials prepared in Examples 1-4 and Comparative Examples 1-2 were used as anodes to fabricate CR2430 coin cells. The specific capacity, initial efficiency, and capacity retention of the first charge were tested, and the test results are shown in Table 1.
[0076] The CR2430 coin cell was fabricated, and the testing conditions were as follows:
[0077] Electrolyte: JN-AHKD-1904
[0078] Formulation ratio: Silicon-carbon anode material: SP: LA132 = 91:3:6
[0079] Counter electrode: Pure lithium sheet
[0080] Charge and discharge regime:
[0081] 1) Let stand for 10 minutes
[0082] 2) Constant current discharge (0.1C, 0.005V)
[0083] 3) Let stand for 10 minutes
[0084] 4) Rate discharge (0.05C, 0.005V)
[0085] 5) Let stand for 10 minutes
[0086] 6) Rate discharge (0.02C, 0.005V)
[0087] 7) Let stand for 10 minutes
[0088] 8) High-rate charging (0.1C, 1.5V)
[0089] Table 1. Test results of relevant performance of silicon-carbon anode materials
[0090]
[0091] As can be seen from Table 1, the electrochemical performance of the silicon-carbon anode material prepared in this invention is significantly better than that of Comparative Examples 1 and 2. This is because the three-dimensional carbon framework structure in the silicon-carbon anode material results in Si particles with a size of less than 10 nm after silane deposition, leading to faster lithium-ion transport and thus improving related performance such as initial charge specific capacity and initial efficiency.
[0092] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.
[0093] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a silicon-carbon composite anode material, characterized in that, Includes the following steps: 1) Si powder is mixed and ground with an organic solvent to obtain a mixed slurry. Then the mixed slurry is mixed with carbon nanotubes and dried to obtain a mixed powder precursor. 2) The mixed powder precursor obtained in step 1) is mixed with an organic carbon source and then sintered and vacuum heat treated in sequence to obtain a porous carbon framework precursor. 3) Deposit silicon particles on the porous carbon framework precursor obtained in step 2) to obtain a silicon-carbon composite anode material; The particle size of the Si powder in step 1) is 3~10μm; The solid content of the mixed slurry in step 1) is 10-50%; the mass ratio of the carbon nanotubes to the mixed slurry is 0.1-5:
100. In step 2), the vacuum degree of the vacuum heat treatment is 0~1000Pa, the temperature of the vacuum heat treatment is 700~1500℃, and the time of the vacuum heat treatment is 3~24h. The steps for depositing silicon particles in step 3) are as follows: first, silicon particles are deposited on the porous carbon framework precursor by a mixture of silane gas and protective gas, and then a carbon layer is deposited by a mixture of carbon source gas and protective gas.
2. The method for preparing a silicon-carbon composite anode material according to claim 1, characterized in that, The organic solvent includes one or more of methanol, ethanol, ethylene glycol, propanol, isopropanol, and propylene glycol.
3. The method for preparing a silicon-carbon composite anode material according to claim 1, characterized in that, The organic carbon source in step 2) includes one or more of the following: asphalt, phenolic resin, sucrose, glucose, and citric acid. The mass ratio of the organic carbon source to the total mass of the organic carbon source and the mixed powder precursor is 45~90:
100.
4. A method for preparing a silicon-carbon composite anode material according to any one of claims 1 to 3, characterized in that, The sintering temperature in step 2) is 300~1000℃, and the sintering time is 3~24h.
5. The method for preparing a silicon-carbon composite anode material according to claim 4, characterized in that, The volume ratio of silane gas to protective gas in the mixture of silane gas and protective gas is 1:1 to 10; the silane gas includes methanesilane and / or ethylsilane, and the protective gas includes one or more of nitrogen, helium, neon and argon. The volume ratio of carbon source gas to protective gas in the mixed gas is 1:1 to 10; the carbon source gas includes one or more of methane, ethane, propane, acetylene and propyne, and the protective gas includes one or more of nitrogen, helium, neon and argon.
6. The method for preparing a silicon-carbon composite anode material according to claim 5, characterized in that, The mass ratio of Si to silicon-carbon composite anode material in the silicon-carbon composite anode material is 1 to 9:
10.
7. The silicon-carbon composite anode material prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
A preparation method of a silicon-carbon composite negative electrode material with a porous structure for lithium ion batteries and an application thereof
CN108987704A
Preparation method of carbon nanotube / silicon composite material
CN112599747A